ANALISIS PENGEMBANGAN DAN KELAYAKAN USAHA OBAT TRADISIONAL JAMU MASYARAKAT KABUPATEN KULONPROGO - Kuswadi Rustam (Kajian Ekonomi dan Bisnis, 2022)
On the economic side, the herbal medicine industry has contributed greatly to national income, increasing people’s welfare and providing employment opportunities. Approximately 99% of herbal ingredients are domestic products and are considered capable of bringing a significant multiplier effect in economic growth in Indonesia, starting from the upstream sector (agriculture) to the downstream sector which includes industry and trade. However, along with the incessant variety of medicines (pharmaceuticals and imported herbal medicines) that are circulating and appear to be attractive to the public, it is not impossible that the demand for herbal medicines as traditional medicines in the last five years has tended to decline. Considering that herbal medicine is a product of the nation’s cultural heritage and has contributed greatly to the creation of domestic workers, the herbal medicine industry, which incidentally is a small and medium industry, must continue to exist amid increasingly fierce competition. Kulonprogo Regency has quite a number of diverse herbal and traditional medicinal plants businesses, most of which are classified as UMKM.. In general, the business diversity is divided into four types of businesses, namely, (1). Liquid herbal medicine business; (2). Herbal medicine business; (3). Herbal dipping business; and (4). Business of herbal tablets/capsules. In order to survive, they need to find some business strategy development to remain viable and profitable. Based on these problems, it is necessary to research the Feasibility and Development Analysis of the Traditional Herbal Medicine Business of the Kulonprogo Regency, with the aim of finding several development strategies and business feasibility. The sample was randomly selected as many as 30 traditional herbal medicine business actors in Kulonprogo Regency. Through the results of the SWOT analysis, there are several business strategies, including (1). Increasing the scale of production and business scale, (2). Following the development of market trends, (3). Marketing innovation and market expansion. (4). Development of licensing legality (certification), such as the legality of an official distribution permit, and being under the guidance of the health office/BPOM. Meanwhile, based on the business feasibility analysis using the Payback Periode (PP) and Benefit Cost Ratio (B/C) method, the liquid herbal medicine business, the brewed herbal medicine business, the dipping herbal medicine business, and the herbal tablet business, capsules are feasible